UMP and TDA seal MoU on seabed - Nor Salwana, Mohammad Idris (2022)
TIOMAN, 10 October 2022 - Universiti Malaysia Pahang (UMP) and Tioman Development Authority (TDA) made history when for the first time held a Memorandum of Understanding (MoU) Signing Ceremony at the seabed, Pulau Tumok, Tioman, Pahang.